The milk macromolecular peptide: preparation and evaluation of antihypertensive activity in rats. Issue 5 (6th May 2020) - Cui, Pengfei; Yang, Xue; Li, Yunliang; Liang, Qiufang; Wang, Yucheng; Lu, Feng; Owusu, John; Huang, Shanfen; Ren, Xiaofeng; Ma, Haile
Abstract : In order to avoid the discomfort of digesting milk protein and make full use of the gastrointestinal digestive function, a milk macromolecular peptide was prepared with ACE inhibitory activity after gastrointestinal digestion as the index. Abstract : In order to avoid the discomfort of digesting milk protein and make full use of the gastrointestinal digestive function, a milk macromolecular peptide was prepared with ACE inhibitory activity after gastrointestinal digestion as the index. Then, the antihypertensive activity of the milk macromolecular peptide in rats was evaluated. The results showed that the ACE inhibitory activity of hydrolysate after simulated gastrointestinal digestion was the highest in which the degree of hydrolysis was 17% and the ACE inhibitory activity reached 78.48%. The optimum enzymatic parameters were obtained with the protein concentration of 3.4%, enzymatic temperature of 55 °C, pH value of 7.0, and 7% enzyme amount using neutral protease. Under these conditions, the ACE inhibitory activity of hydrolysate after simulated gastrointestinal digestion was as high as 89.49%. Compared to traditional peptides, the ACE inhibitory activity of the macromolecular peptide increased after simulated gastrointestinal digestion. After 4 weeks of gavage tests of the milk macromolecular peptide, the blood pressure of rats with spontaneous hypertension dropped to below 140 mmHg, with a decrease of 60 mmHg. The antihypertensive effect of the milk macromolecular peptide was similar to that of captopril. The milk macromolecular peptide decreased the blood pressure of spontaneously hypertensive rats by inhibiting the ACE activity of the lung, kidney and arteries, and regulating the content of the signal factors of endothelin, NO, angiotensin II and renin in serum indicators. These results indicated that the macromolecular ACE inhibitory peptide with an antihypertensive effect could be prepared by the enzymatic hydrolysis of milk protein to realize the full utilization of protein resources.